2019
DOI: 10.15294/jbe.v8i2.28016
|View full text |Cite
|
Sign up to set email alerts
|

Development of Interactive Multimedia for Human Reproduction System in Junior High School

Abstract: The study was aim to find out the effectiveness of the multimedia interactive for human reproduction system learning.  The research was done at Junior High School 5 Pemalang with the design of research is Research and Development (R&D). The small scale trial of the product was done in 23 students with proportionate stratified random sampling method. The larger scale trial of the product was done in IX A class with Purposive Sampling Method and One Group Pre-test Post-test Experimental Design. The assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
1
0
1
Order By: Relevance
“…Although the parts of the interactive multimedia layout have a harmonious color composition, clarity, and contrast, interactive multimedia has become an excellent medium. A visually appealing display with clear and bright pictures might help students focus on learning to grasp topics (Puspitasari, Indriyanti & Nugrahaningsih, 2019). This was consistent with the belief that the essential aspect of creating visual design goods was the use of color.…”
Section: Analysis Stagesupporting
confidence: 78%
“…Although the parts of the interactive multimedia layout have a harmonious color composition, clarity, and contrast, interactive multimedia has become an excellent medium. A visually appealing display with clear and bright pictures might help students focus on learning to grasp topics (Puspitasari, Indriyanti & Nugrahaningsih, 2019). This was consistent with the belief that the essential aspect of creating visual design goods was the use of color.…”
Section: Analysis Stagesupporting
confidence: 78%
“…In addition, multimedia can create a positive mood for students (Khan et al, 2019;Liew & Tan, 2016;Warsono et al, 2020), so they are more engaged in learning physics. This argument is supported by (Puspitasari et al, 2019), who found that 88% of multimedia can motivate students in learning physics. (Nurnasari & Nurindah, 2018) also argued that the use of multimedia would facilitate the teacher in the learning process and students in participating in learning resulting in the increased motivation.…”
Section: A Introductionmentioning
confidence: 83%
“…Pemilihan bahan ajar dan cara penyampaian materi berpengaruh dalam pemahaman siswa pada materi sistem reproduksi manusia (Mondher, Naima, Sami, & Lassaad, 2010). Multimedia interaktif yang menampilkan animasi, video, gambar, dan pertanyaan lebih memudahkan pembaca untuk memahami materi sistem reproduksi manusia (Puspitasari, Indriyanti, & WH, 2019). Tiga faktor penting dalam pembelajaran sistem reproduksi manusia, yakni: pengetahuan ilmiah, keterampilan mengajar, dan konsep dasar dari guru (Špernjak & Šorgo, 2018).…”
unclassified